Intelligent tutoring system of the university department - A. S. Aleshchenko; V. M. Trembach (Открытое образование (Москва), 2016)
The aim of the research is intelligent tutoring system for planning and development of individual learning programs for students. One of the important components of modern training programs is the individual practice programs that are formed from the first course and built up in the process of learning in the subsequent courses. Each individual practice program is formed on the basis of the Working program of practice for a specific group. At later practice stages planning and adjustment of the individual program are worked out for a particular student.The agent-oriented approach for the planning of individual learning programs is used for the formation of individual practice program. Agents of the intelligent learning systems are created according to the requirements of service-oriented architecture. To apply knowledge there used an integrated approach to represent knowledge.As a result of research, the authors propose the architecture of intelligent educational systems of the University Department, using the repository of learning objects, telecommunication systems and such agents as: the learner, the assessment of the student’s knowledge, the formation of individual programs for learning, the personal learning environment, the methodical support, the businesses. The authors demonstrate the possibility for the formation of individual practice programs using an agent of the methodical support.Application of the approaches and technologies which were considered in the article will allow to solve problems of the formation of individual practice programs. The use of such applications will extend the possibilities of intelligent tutoring systems of the University departments.